Investigating Students' Perceptions of Online Learning Use as a Digital Tool for Educational Sustainability During the COVID-19 Pandemic - Alqahtani, Mohammed Ayid; Alamri, Mahdi Mohammed; Sayaf, Amer Mutrik; Al-Rahmi, Waleed Mugahed (Frontiers in Psychology, 2022)
Previous research on e-learning in underdeveloped countries has seldom taken a comprehensive approach. A literature review of recent published research in the field of e-learning usage during the COVID-19 epidemic is also included in this study. Therefore, the aim of this study is to look at the technology acceptance model (TAM) and information systems (IS) performance models to see how system quality (SYQ), service quality (SEQ), and quality of life (QoL) are related, as well as the mediating impact of perceived ease of use (PEU) and perceived usefulness (PU), affect students' behavioral intention to use (BIU), and actual use of an e-learning system (AUE) as sustainability for education during the COVID-19 pandemic. Path analysis and structural equation modeling (SEM) were used to evaluate the research model using data from e-learning users obtained through a survey. The participants were e-learning users from two Saudi Arabian public universities. The findings revealed that perceived usefulness and ease of use were both positively correlated and influenced by system quality, service quality, and quality of life in education, and that perceived ease of use and perceived usefulness were positively influenced by students' behavioral intention to use and actual use of an e-learning system. In the sense of e-learning in developing countries, previous studies rarely looked at an integrated model. This paper also attempts to provide a study recently published in the area of e-learning system use as sustainability for education during the COVID-19 pandemic. There is a lot of re-search going on.